Analysis of Occupational Safety and Health (OSH) Risks in Hospitals: Literature Review - Widi Mahasih Pramusiwi; Widodo Hariyono; Rochana Ruliyandari (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Introduction: As one of the workplaces that poses significant risks to occupational safety and health, hospitals have the potential for the emergence of infectious diseases among staff, patients, and even visitors. Essentially, all healthcare workers, including healthcare professionals, are at risk of being exposed to hazards in the workplace. Objective: To determine the extent and types of health and safety risks present in Indonesian hospitals, researchers conducted further assessment through a systematic literature review. Method: Data collection was carried out using specified categories on the Google Scholar search page, while the data filtering method was conducted by applying the PRISMA analysis method, resulting in six research articles being reviewed in this study. Result: From the various studies reviewed, it is known that occupational health and safety hazards have the potential to result in numerous risks, including bacteria; cough and cold; dizziness; sneezing; Covid-19; animal disturbances; musculoskeletal disorders; hepatitis A; hepatitis B; HIV; nosocomial infections; fungi; falls; fatigue; heat; medical waste fluid contamination; medical waste; bruises; sore eyes; muscle pain; low back pain; joint pain; panic; exposure to hazardous and toxic materials; poor lighting; incorrect posture; attacks from patients; shortness of breath; work stress; scratches; falls from stairs; slips; being hit; stumbling; paper cuts; electric shocks; viral infections; being hit by objects; needle pricks; typhus; tuberculosis; and other viruses. These risks are categorized as physical, chemical, biological, ergonomic, and psychological hazards. Additionally, each risk has different levels of severity (high, medium, low) in each case. Conclusion: Occupational health and safety hazards in hospitals encompass a wide range of risks, categorized into physical, chemical, biological, ergonomic, and psychological hazards. These include infectious diseases like Covid-19, hepatitis, and tuberculosis; physical injuries from falls, slips, and needle pricks; exposure to hazardous chemicals; ergonomic issues; and psychological stress.